Návrh železničního rámového mostu - Findura, David (Vysoké učení technické v Brně. Fakulta stavební, 2018)
Tato práce řeší návrh dvoukolejného železničního rámového mostu přes údolí. Ze tří navrhovaných variant byla zvolena varianta 1 - předpjatá rámová konstrukce proměnného trámového průřezu. Dle platných norem EN byla konstrukce navržena a posouzena na mezní stavy použitelnosti a mezní stavy únosnosti.

This thesis deals with a design of a two-track railway frame bridge over a valley. Out of three proposed variants was chosen the variant number 1 - prestressed frame construction with variable beam section. According to actual EN standards the construction was designed and assessed to the serviceability limit state and the ultimate limit state.
Design of a railway frame bridge
Keywords: Mostní konstrukce; předpjatá konstrukce; železniční most; rámový most; železobeton; statický výpočet; ztráty předpětí; Bridge construction; prestressed; construction; railway bridge; frame bridge; reinforced concrete; static calculation; losses in prestress